Determinación en la presencia de Sarna Sarcóptica en perros en la Parroquia Barreiro de la Ciudad de Babahoyo - Baldeon Torres, Allison Noemi (2023)
Sarcoptic mange is a skin disease caused by Sarcoptes scabiei var. mites, which in dogs can cause intense pruritus and alopecia, the most common being the so-called scabies, which in the first instance affects those who have direct contact with the infested dogs. The descriptive percentage method will be used where the sampling of 80 dogs is originated by ectoparasites are considered one of the zoonotic pathologies where the result analysis showed that 2.50% of the dogs sampled in the parish of Barrero, city of Babahoyo, were positive for scabies mites. On the other hand, 97.50% of the dogs analyzed showed no evidence of the disease. Therefore, this research will be carried out with the purpose of determining the presence of sarcoptic mange in dogs in the parish of Barreiro in the city of Babahoyo, in order to achieve a preventive and investigative impact at the level of public health and animal welfare.